Effect and mechanism of resveratrol on drug resistance in human bladder cancer cells - Wang, Shanshan (Mol Med Rep, 2017)
Multidrug resistance (MDR) is a significant barrier to the effective treatment of bladder cancer. In order to improve the management of bladder cancer, it is crucial to identify strategies that may reverse MDR. The effects of three herbal medicines, ginsenoside Rh2, (−)-epigallocatechin gallate (EGCG) and resveratrol (RES) on bladder cancer were determined. The effect of these three herbal medicines against the drug resistance in adriamycin (ADM)-resistant pumc-91 cells (pumc-91/ADM) was assessed using the Cell Counting Kit-8 cell proliferation assay system. Cell cycle distribution analysis was performed using flow cytometry following treatment with RES. The mRNA and protein expression levels of multidrug resistance protein 1 (MRP1), lung resistance protein (LRP), glutathione S-transferase (GST), B cell leukemia/lymphoma-2 (BCL-2) and topoisomerase-II (Topo-II) were evaluated using reverse transcription-quantitative polymerase chain reaction and immunofluorescence, respectively. RES enhanced the cytotoxicity of anticancer agents on pumc-91/ADM cells; however, Rh2 and EGCG were unable to induce a similar effect. Additionally, RES treatment led to S phase cell cycle arrest accompanied by a decrease in the number of cells in the G1 phase. A significant decrease of MRP1, LRP, GST, BCL-2 levels and an increase of Topo-II levels were observed in RES groups compared with the control group. RES effectively reversed ADM resistance in pumc-91/ADM cells and the underlying molecular mechanism may be associated with the alteration of MRP1, LRP, GST, BCL-2 and Topo-II expression levels. Therefore, RES may be a potential candidate for reversing drug resistance in bladder cancer chemotherapy.